NILAI EDUKATIF MU'JIZAT AL-QUR'AN DARI PERSPEKTIF INFORMASI GAIB DALAM PEMBENTUKAN KARAKTER ANAK - Muhammad Arif Halomoan Hsb; Rahimatun Munasyaroh; Fika Maharani; Nadia Nadia; Nurul Aini Siregar (LPPM IAD Probolinggo, 2026)
The miracle of the Qur'an from the perspective of the unseen (i'jāz al-ghaybī) is one of the strongest proofs of its divine origin. This aspect is reflected in its accurate accounts of past events, unseen realities, and future occurrences that were later confirmed by historical evidence. This study aims to examine the concept of i'jāz al-ghaybī, identify its principal forms, and explore its significance in Islamic scholarship. A qualitative approach employing library research was used. Data were collected from the Qur'an, classical and contemporary tafsir literature, books on i'jāz al-Qur'an, and relevant scholarly articles, and were analyzed using a descriptive-analytical method. The findings reveal three major dimensions of the Qur'an's unseen miracles: narratives of past events beyond the Prophet Muhammad's knowledge, predictions of future events that were historically fulfilled, and descriptions of unseen realities beyond human perception. These findings affirm that i'jāz al-ghaybī serves not only as evidence of the authenticity of divine revelation but also as a theological and educational foundation that strengthens faith and encourages deeper understanding of the Qur'an. Consequently, this dimension of Qur'anic miracle remains relevant to contemporary Islamic studies.